Sei sulla pagina 1di 6
• • • •

V

= {p(x) P 3 [x] / p (1) = p(0) + p (1) = 0}

V

P 3 [x]

W = 1 + 3x 2x 2 + x 3 , 3 + 10x 4x 2 + 4x 3 , , 2 + 8x + 4x 3

P 3 [x]

α = {(1, 1, 1) , (2, 0, 1) , (1, 2, 1)} β [I]

α

β

P 3 [x]

= {(1, 1, 2); (0, 1, 1); (1, 1, 1)}

U 1 = 3 2x + x 2 + x 3 , 1 + x 2 x 3 , 2 x + x 3

U 2 = 2 x + 2x 2 + x 3 , x x 3 , 3 2x + 3x 2 + x 3

 

(a)

U 1 U 2 U 1 + U 2 U 1 U 2

 

(b)

U 3 (U 1 U 2 ) U 3 = P 3 [x]

 

B = {u 1 , u 2 , u 3 , u 4 } V B = {v 1 , v 2 , v 3 , v4}

B

= {w 1 , w 2 , w 3 , w 4 }

 
 

v 1 = (0, 1, 0, 3)

;

v 2 = (1, 1, 0, 0)

;

v 3 = (2, 0, 1, 2)

;

v 4 = (1, 1, 1, 1)

w 1 = (2, 2, 0, 1)

;

w 2 = (1, 1, 1, 0)

;

w 3 = (3, 0, 1, 1)

;

w 4 = (0, 2, 1, 1)

 

B

 

(a)

B B V

 

(b)

B B

(c)

B x B (2, 1, 0, 1)

T : V W α = {v 1 , v 2 , v 3 , v 4 } V β = {w 1 , w 2 , w 3 , w 4 } W

B W

[T]

[T] β

α

β

α =

=

1

0

0

1

0

0

0

1

0

1

1

0

0

0

1

1

1

1

0

1

1

0

0

1

T : P 2 [x] R 3 T

α = {1, x, x 2 } R 3 β = {(1, 0, 0); (0, 1, 0); (0, 0, 1)}

T (1 + x x 2 ) = (1, 0, 1)

T(x 2 x) = (1, 1, 1)

T (2 + x 2x 2 ) = (1, 1, 2)

T : R 3 R 2 T (x, y, z) = (2x + y, 3z)

(a)

(b)

α = {(1, 2, 1), (0, 1, 0), (3, 1, 1)} β = {(0, 2), (1, 1)}

(c)

α = {(1, 1, 1), (0, 1, 0), (0, 0, 1)} β = {(1, 3), (1, 0)}

T : R 2 R 3

T (x, y) = (2x y, x + y, 2y x)

(a)

[T ] α β α β R 2 R 3

(b)

Ker(T ) Img(T )

(c)

α = {(2, 1); (0, 3)}

= {v 1 , v 2 }

β = {(1, 1, 1); (2, 0, 1); (0, 0, 2)} = {w 1 , w 2 , w 3 }

T ( 2 v 1 3 v 2 )

1

1

V T : V

W

β

= {v 1 , v 2 , v 3 , v 4 } β = {w 1 , w 2 , w 3 } V

W

W

Ker(T ) = v 1 + v 2 + v 3 , v 4 ; T(v 1 + 2v 2 ) = w 1 w 2 ;

T(v 2 ) = w 1 + w 2

T β β

T : M 2×2 M 2×2 T (X) = AXB

A =

1

0

2

1

;

1

2

1

0

T M 2×2 T T

V T : V V B V A = [T ] B B A

(a)

A

(b)

A T A

(c)

(A + I)

a R A =

0

1

0

dy

dx =

1 x + y 1

2

x + 2

2

y(0) = 3

0

0

1

0

2a 2

3a

3xy + cos(x)

x

dx + 2x 2 + sin(x) xy dy = 0

 

t = 0 A B A 10 B

1

(a)

(b)

(c) t = t 2 0

t = t 0

t < t 0

(2y 6x)dx + 3x 4x 2

y

dy = 0

(a)

µ(x, y) = h(xy 2 )

(b)

h(xy 2 )

(c)

y + y

= ln(x)

x x

y 2

t = 0 Q 0 litros/min

(a)

t

(b)

t

(a) 1 + ln(x) +

(b)

dx = x y + 2

dy

x y + 3

y

x dx = (1 ln(x)) dy

y xy 2 ln(x) dx + xdy = 0

(a)

(b)

µ(x, y) = φ(xy)

(c)

{y + x(x 2 + y 2 ) 2 }dx + {y(x 2 + y 2 ) 2 x}dy = 0

(a)

(b)

u(x, y) = φ(x 2 + y 2 )

(c)

L e ax x

0

e at F (t)dt = s F(s) + a

(a)

(b)

(c)

(d)

(e)

L x te 2t sin(t)dt

0

L

{f (x)} f (x) =

L 1

(s 2 + 1) 2

s

L 1 e 2s

s

2

s + 1

e

s

x 2

0 < x < 2

4x

x > 2

f (x)

Y 2 1 2 4
Y
2
1
2
4

X

y = x

(1 x 2 )y 2xy + 2y = 0

y (x) + 2y (x) + 5y(x) = 0

;

y(0) = 0

;

y (0) = 1

y (x) + 9y(x) = 3 sin(2x)

2

;

y(0) = 0

;

y (0) = 0

y (x) + 4y(x) = f (x) y(0) = y (0) = 0 f (x) =

0

0 x 3

x

x 3

(a)

y + 3y + 2y = e 2x + x 2

(b)

y 2y + y = 3x + 25 sin(3x)

(x 2 + 1)y 2xy + 2y = 6(x 2 + 1) 2 y 1 (x) = x

xy (x) + (x 1)y (x) y(x) =

x 2

;

y(1) = 0

;

y (1) = 1

y(x) = e x

y(0) = 1 y (0) = 1

y (x) + 4y (x) + 4y(x) =

0

e (x1)

,

,

x 2 x > 2

f(x) =

y (x) + 2y (x) 3y(x) = 3f(x)

0

x 2 2x + 1

4x 8

,

,

,

x 1 1 < x 3

x > 3

y(0) = y (0) = 0

4x 4 y (x) + 8x 3 y (x) + y(x) = tan

(a)

2x

1

y (x) + tan(x)y (x) 6 cot 2 (x)y(x)

= 0

y 1 (x) = sin 3 (x)

(b) y (x) 2y (x) + 10y(x) = 2x 2 + 2x 8

y (x) + 4y(x) = 3 sin(x)

0

;

0 x 2π

;

x > 2π

; y(0) = y (0) = 0

I

I (t) + 4I(t) = g(t)

g(t) =

1

1

0

;

;

;

;

I(0) = I (0) = 0

0 < t < π π t 2π t > 2π

R 3 λ

= (2, 1, 0); φ = (1, 0, 1); η = (0, 1, 1); ρ = (1, 1, 1)

L =

{λ, φ}

S = {ρ, η}

α S R 3 = L + {α} L {α} = 0

 

u = (u 1 , u 2 , u 3 ) x = (x, y, z) R 3

 
 

u × x

=

(u 2 z u 3 y, u 3 x u 1 z, u 1 y u 2 x)

u = (1, 2, 3) T = u × x T : R 3 −→ R 3

T

T R 3

dim(ker(T )) dim(Img(T ))

V

K α = {u 1 , u 2 , u 3 , u 4 }

v 1 = 2u 1 + u 2 u 3

;

v 2 = 2u 1 + u 3 + 2u 4 ; v 3 = u 1 + u 2 u 3 ; v 4 = u 1 + 2u 3 + 3u 4

β

α (1, 2, 0, 1)

=

{v 1 , v 2 , v 3 , v 4 }

(a) α

A =

1

0

0

1

1

0

V

β v

2 α α

1

 

(b) y + y

x

= ln(x)

x

·

y 2

m 3 m 3 t = 0 m 3 m 3

xy (x) + (2x 1)y (x) 2y(x) = x 2 e 3x

;

x > 0

;

y 2 = y 2 = 0

1

1

y 1 (x) = e mx m R

y + 4xy + (6 + 4x 2 )y = x 2 e x 2

(a)

y(x) = u(x)e x 2 u(x)

(b)

y(x) y(0) = 1 y (0) = 0

(a) y (x) + 2y(x) = cos(2x) + µ(x 2) y (0) = y(0) = 0

(b) L {µ(x a)f (x a)} = e as F (s) L 1

3s

s 2 + 6s + 10

e